Employee Job Performance Studies in the Military Context: A Bibliometric Analysis - Rohitha Abeysinghe; Anuradha Iddagoda; Hiranya Dissanayake; W. P. Richard Wickramaratne (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
Employee job performance is how an employee performs his/her job and completes the necessary tasks. Employee job performance is the secret to success for any organisation. The aim of this bibliometric analysis is to identify primary topics and present the dynamic in the field of employee job performance and to make recommendations for future research directions. The bibliometric analysis was conducted with the use of 421 articles found in the Scopus index. The study excludes studies that were undertaken in languages other than English. In the context of the military, the majority of study on employees' job performance is concentrated on the connection between psychological factors and working conditions. Finally, this study suggests potential areas for further research undertaken by scholars. Keywords: bibliometric analysis, employee job performance, military context   Badania wydajności pracy w kontekście wojskowym: analiza bibliometryczna Wydajność pracownika to sposób, w jaki zatrudniona osoba wykonuje swoją pracę i wypełnia wskazane zadania. Wydajność pracownika to sekret sukcesu każdej firmy. Celem niniejszej analizy bibliometrycznej jest zidentyfikowanie głównych tematów i przedstawienie dynamiki obszaru wydajności pracownika, a także wskazanie zalecanych kierunków przyszłych badań. Niniejszą analizę bibliometryczną przygotowano w oparciu o 421 artykułów skatalogowanych w bazie Scopus. Z analizy wyłączono badania przygotowane w językach innych niż angielski. W kontekście wojskowym większość badań dotyczących wydajności pracowników skoncentrowanych jest na związkach między czynnikami psychologicznymi i warunkami pracy. Badanie to sugeruje także potencjalne obszary dalszych badań naukowych.